Candesartan, rather than losartan, improves motor dysfunction in thioacetamide-induced chronic liver failure in rats - Murad,H.A. (2017)
Minimal hepatic encephalopathy is more common than the acute syndrome. Losartan, the first angiotensin-II receptor blocker (ARB), and candesartan, another widely-used ARB, have protected against developing fibrogenesis, but there is no clear data about their curative antifibrotic effects. The current study was designed to examine their effects in an already-established model of hepatic fibrosis and also their effects on the associated motor dysfunction. Low-grade chronic liver failure (CLF) was induced in 3-month old Sprague-Dawley male rats using thioacetamide (TAA, 50 mg·kg−1·day−1) intraperitoneally for 2 weeks. The TAA-CLF rats were randomly divided into five groups (n=8) treated orally for 14 days (mg·kg−1·day−1) as follows: TAA (distilled water), losartan (5 and 10 mg/kg), and candesartan (0.1 and 0.3 mg/kg). Rats were tested for rotarod and open-field tests. Serum and hepatic biochemical markers, and hepatic histopathological changes were evaluated by H&E and Masson's staining. The TAA-CLF rats showed significant increases of hepatic malondialdehyde, hepatic expression of tumor necrosis factor-α (TNF-α), and serum ammonia, alanine aminotransferase, γ-glutamyl transferase, TNF-α, and malondialdehyde levels as well as significant decreases of hepatic and serum glutathione levels. All treatments significantly reversed these changes. The histopathological changes were moderate in losartan-5 and candesartan-0.1 groups and mild in losartan-10 and candesartan-0.3 groups. Only candesartan significantly improved TAA-induced motor dysfunction. In conclusion, therapeutic antifibrotic effects of losartan and candesartan in thioacetamide-induced hepatic fibrosis in rats are possibly through angiotensin-II receptor blocking, antioxidant, and anti-inflammatory activities. Improved motor dysfunction by candesartan could be attributed to better brain penetration and slower “off-rate” from angiotensin-II receptors. Clinical trials are recommended.